Hydration status assessment among elite youth amateur boxers - Zubac, D.; Karnincic, H.; Zaja, M. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: Weight cutting is a common practice in amateur boxing with the purpose of taking advantage of rivals competing in weight divisions below the athlete's normal weight. Dehydration is a common weight-manipulating technique in boxing, and is known as a serious health-threatening behavior. In this study, we investigated field hydration status differences between the weight class categories in elite junior boxers.